Handbuch Europäische Sprachkritik Online Sprachnormierung und Sprachkritik - Felder, Ekkehard; Schwinn, Horst; Busse, Beatrix; Eichinger, Ludwig M.; Große, Sybille; Gvozdanović, Jadranka; Jacob, Katharina; Radtke, Edgar (Handbuch Europäische Sprachkritik Online, 2017)
The process of setting norms for language and language use is closely related to critique of language and its use. The German term Sprachnormenkritik as yet has no equivalent in English, French, Italian, or Croatian linguistics. Notwithstanding, the concept of ›critique of language norms‹, or aspects of it, have been debated in all these languages for centuries.